Antimicrobial resistance of microorganisms in peritonitissecondary to peritoneal dialysis at Almanzor Aguinaga -Asenjo Hospital, EsSalud - Lambayeque 2019 - 2021 - Díaz-Muñoz, Juan C. (2025)
Objective: To determine antimicrobial resistance in secondary peritonitis in patients with chronic kidney disease (CKD) undergoing peritoneal dialysis at the Almanzor Aguinaga- Asenjo Hospital EsSalud-Lambayeque between 2019 and 2021. Material and methods: Descriptive and retrospective study, on 135 peritonitis episodes according to case records. Forty-seven episodes from 33 patients met inclusion criteria, and 88 episodes were excluded due to lack of reporting or bacterial isolation. Data was analyzed using the R studio 4.1.3 statistical package for Windows, expressing values as percentage and frequency. Results: More than half of patients (57.6%) were male, and median age was 54 years; 47.2% were diabetic and had high blood pressure. Oxacillin, vancomycin, gentamicin, and ciprofloxacin resistant coagulase-negative Staphylococcus were isolated (34%); cefazolin, ampicillin/sulbactam, and cotrimoxazole resistant Pseudomonas aeruginosa (21.3%); cotrimoxazole, ciprofloxacin, ceftriaxone, and cefepime resistant Escherichia coli (19.2%); and oxacillin and vancomycin resistant Staphylococcus aureus (10.6%) were also isolated. Conclusions: The most common antimicrobial-resistant microorganism is coagulase-negative Staphylococcus, found to be resistant to oxacillin, vancomycin, gentamicin, and ciprofloxacin.